Facile and Green Synthesis of Graphene-Based Conductive Adhesives via Liquid Exfoliation Process - Wu, Jhao-Yi; Lai, Yi-Chin; Chang, Chien-Liang; Hung, Wu-Ching; Wu, Hsiao-Min; Liao, Ying-Chih; Huang, Chia-Hung; Liu, Wei-Ren (Nanomaterials (Basel, Switzerland), 2018)
In this study, we report a facile and green process to synthesize high-quality and few-layer graphene (FLG) derived from graphite via a liquid exfoliation process. The corresponding characterizations of FLG, such as scanning electron microscopy (SEM), transmission electron microscope (TEM), atomic force microscopy (AFM) and Raman spectroscopy, were carried out. The results of SEM show that the lateral size of as-synthesized FLG is 1–5 μm. The results of TEM and AFM indicate more than 80% of graphene layers is <10 layers. The most surprising thing is that D/G ratio of graphite and FLG are 0.15 and 0.19, respectively. The result of the similar D/G ratio demonstrates that little structural defects were created via the liquid exfoliation process. Electronic conductivity tests and resistance of composite film, in terms of different contents of graphite/polyvinylidene difluoride (PVDF) and FLG/PVDF, were carried out. Dramatically, the FLG/PVDF composite demonstrates superior performance compared to the graphite/PVDF composite at the same ratio. In addition, the post-sintering process plays an important role in improving electronic conductivity by 85%. The composition-optimized FLG/PVDF thin film exhibits 81.9 S·cm−1. These results indicate that the developed FLG/PVDF composite adhesives could be a potential candidate for conductive adhesive applications.